Efeitos do treinamento aeróbico na qualidade de vida em idosos, um estudo randomizado e controlado - Alabarse, Silvio Lopes [UNIFESP] (2016)
The world?s population is ageing, in Brazil, the increase in the life expectancy is also due to advances in health care. Among the factors that determine whether the aging is positive or not, the physical health is related to the possibility of managing their own choices with greater or less dependence. Aging causes physiological changes which can be reduced with physical exercises. However, for a predominantly aerobic training prescribed by professionals, is relevant to be aware of an appropriate instruction in order to generate benefits and enhance the autonomy and the independence of elderly. The hypothesis of the study was that seniors, when included in a physical exercises program, could improve their physical function, the quality of life and their functional autonomy. To check the effects of aerobic training on their quality of life, it was done a physical workout with 69 cases, both genders and average age of 68 years old. The training group (TG) was composed by 40 people undergoing continuous walking at an intensity of 50% to 75% of HRMáx., for 30 minutes, three times a week. In the control group (CG), 29 patients supervised and oriented to not doing physical exercises involving walking. Both answered the questionnaire about quality of life called WHOQUOL-OLD and performed maximal exercise test before and after training. Statistics, descriptive and analytical analyses were made; calculus performed by ?Statistical Package for the Social Sciences (SPSS, v.20.0)?; significance level of p?0,05; and study approved by the Research and Ethics Committee of the institution linked to the study. VO2peak relative of TG and CG did not change [TG, 23,67ml.Kg-1.min-1 (± 5,2) to 24,46ml.Kg-1.min-1 (± 5,6) (p = 0,06 / CG, 23,61ml.Kg-1.min-1 (± 4,9) to 23,57ml.Kg-1.min-1 (± 4,6) (p = 0,95)]. The quality of life did not improve in CG and TG [CG, 64,9 (± 12,0) to 63,1 (± 13,1) (p = 0,41) / TG, 65,5 (± 14,0) to 65,6 (± 16,0) (p = 0,95)]. Relative oxygen consumption in resting condition in TG and CG did not improve [TG, 5,93ml.Kg-1.min-1 (± 1,8) to 6,89ml.Kg-1.min-1 (± 2,3) (p = 0,75 / CG, 5,62ml.Kg-1.min-1 (± 2,1) to 6,23ml.Kg-1.min-1 (± 1,6) (p = 0,28)]. The muscular strength of the lower limbs raised in TG, while CG did show progress [TG, 12,0 units (± 2) to 12,5 units (± 2,5) (p = 0,001) / CG, 11 units (± 2,0) to 12 units (± 2,4) (p = 0,20)]. The amount of depressive symptoms in patients of TG decreased, compared to CG [TG, 2,7 units (± 2,4) to 1,9 units (± 1,9) (p = 0,04 / CG, 2,9 units (± 2,7) to 2,9 units (± 2,4) (p = 0,94)]. The variables mobility and risk of falls in TG had positive changes in comparison to CG, which did not show changes [TG, 454s (± 65,3) to 417s (± 68,9) (p = 0,001 / CG, 478s (± 116,7) to 451s (± 55,9) (p = 0,12)]. Difficulties regarding the daily activities for the TG decreased, while CG did not present changes [TG, 2,3 (± 2,7) to 1,2 (± 1,8) (p = 0,002 / CG, 2,1 (± 2,3) to 2,4 (± 2,4) (p = 0,35)]. TG reported less complaints of pain, while CG remained without changes [TG, 4,3 (± 3,1) to 2,9 (± 3,0) (p = 0,006 / CG, 4,4 (± 3,2) to 4,2 (± 3,2) (p = 0,68)]. We conclude that a physical training involving walking for elderly, with a simple prescription during a short period of training, despite not causing, in a wide form, physiological changes in aerobic capacity and in the quality of life, is capable of producing functional, sensitive, social and emotional improvements. Furthermore, surely this special population can enjoy a successful and independent aging through physical exercise.